2009
DOI: 10.4049/jimmunol.0801217
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of IL-6 Trans-Signaling in Colonic Epithelial Cells, Induced by the IL-6/Soluble–IL-6 Receptor Derived from Lamina Propria Macrophages, on the Development of Colitis-Associated Premalignant Cancer in a Murine Model

Abstract: Activation of the IL-6/Stat3 via IL-6 trans-signaling plays an important role in the pathogenesis of inflammatory bowel disease. Colitis-associated cancer (CAC) is a large bowel cancer and occurs with long-standing inflammatory bowel disease. The role of the IL-6/Stat3 in the development of CAC has not been fully understood. We investigate whether IL-6 trans-signaling contributes to the development of CAC using a mouse colitis-associated premalignant cancer (CApC) model. Chronic colitis (CC) was induced in BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 49 publications
10
133
0
Order By: Relevance
“…SPINK1 protein is secreted from the liver in the systemic circulation as one of the acute-phase proteins to inhibit trypsin activity in tissues. In addition, it has already been reported that IL6 is induced in DSS colitis mice (35). In the current study, we showed that Spink3 was overexpressed at the regenerative stage in DSS colitis and that it may have contributed to the proliferation and repair of the colonic cells.…”
Section: Discussionsupporting
confidence: 50%
“…SPINK1 protein is secreted from the liver in the systemic circulation as one of the acute-phase proteins to inhibit trypsin activity in tissues. In addition, it has already been reported that IL6 is induced in DSS colitis mice (35). In the current study, we showed that Spink3 was overexpressed at the regenerative stage in DSS colitis and that it may have contributed to the proliferation and repair of the colonic cells.…”
Section: Discussionsupporting
confidence: 50%
“…The amounts administered were sufficient to block IL-6 trans-signaling mediated processes in other mouse models. 25,26 In summary, IL-6 trans-signaling does not seem to play a role in this model of plasmacytoma development, however, it could be of importance in addressing other gp130 positive cells in the bone marrow, such as stromal cells and osteoclasts. 27 The activation of gp130 is a major event in controlling the growth and survival of malignant plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…sIL-6Ra can also bind IL-6, to form the IL-6/sIL-6Ra complex that interact with membrane gp130 to induce signal transduction. The importance of IL-6 trans-signaling in chronic colitis and CAC development has been well demonstrated (6,22). TACE plays a major role in the inflammatory processes by promoting the shedding of the extracellular domain of several transmembrane proteins such as receptors and adhesion molecules (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…TACE plays a major role in the inflammatory processes by promoting the shedding of the extracellular domain of several transmembrane proteins such as receptors and adhesion molecules (26,27). In the CAC model, tumor epithelial cells express high level of TACE, which control IL-6R shedding and thus IL-6 trans-signaling (6,22). The specific inhibition of this signaling by the antibody against IL-6Ra or the blockade of sIL-6Ra using gp130-Fc prevented CAC tumorigenesis (6).…”
Section: Discussionmentioning
confidence: 99%